The Role of Vitamin D in Immune Balance and Inflammation - Handayani, Kurnia Maidarmi; Sari, Widia; Khudri, Ghaniyyatul; Dhuha, Alief (Health and Medical Journal, 2025)
Vitamin D, traditionally known for its role in bone health, is increasingly recognized as a crucial regulator of immune balance and inflammation. This review explores the mechanisms by which vitamin D influences both innate and adaptive immune responses, with a focus on immune cells like macrophages, dendritic cells, T cells, and B cells. Vitamin D, through its active form, calcitriol, modulates immune cell function by binding to the Vitamin D receptor (VDR), which impacts cytokine production and inflammatory pathways. Notably, vitamin D promotes anti-inflammatory effects by shifting immune responses towards a regulatory phenotype, reducing pro-inflammatory cytokines while enhancing anti-inflammatory signals. This regulatory potential highlight vitamin D’s therapeutic value for inflammatory and autoimmune diseases. Further research is essential to determine optimal vitamin D dosing and its implications across diverse populations.